Analysis Water Pump Control System Using PID Based on PLC and HMI - Rachmawati, Angraini; Marindani, Elang Derdian; Sanjaya, Bomo Wibowo (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2025)
The liquid"™s level is given particular notice, whereby the liquid"™s level is maintained at a certain level to meet the volume requirement. The implementation liquid level control system involves the use of water pumps in water supply management at Selat Panjang, Pontianak. The water in reservoir must be maintained in a specific level range. If the water is too high or too low, it will significantly affect the reliability and safety of the pumps. Water level control in a reservoir is carried out by adding a controller to the system. The control equipment used is a PLC (Programmable Logic Controller). Then, mathematical calculations will be carried out using MATLAB. Calculations are carried out using 3 methods, namely the manual method, the Ziegler"“Nichols method, and auto-tuning method. When applying the three methods to the system, the observed manual method demonstrated stability with a P value of 1, I value of 20, and D value of 25, approaching the setpoint at 2.21 meters with an error of ±1.1 meters. The Ziegler"“Nichols had the longest rise time but achieved the water level close to the setpoint with an error of ±0.1 meter. The auto-tuning method exhibited a relatively fast rise time of approximately 1 minute and 20 seconds. However, the water level increasingly deviated from the desired setpoint. Implementation results concluded that the Ziegler"“Nichols is the most suitable for the system. This research is expected to enhance the efficiency, safety, and reliability of the pump usage at Perumdam Tirta Khatulistiwa.